Integrating Ethnic Narratives into EFL Teaching: A Reflective Case Study in a Chinese University Setting - Zuo, Miaomiao (Pacific International Journal, 2024)
In the continually developing field of English as a Foreign Language (EFL) teaching, integrating ethnic narratives has become increasingly important to enhance learning outcomes and foster intercultural competence. This reflective case study explores the effectiveness of incorporating ethnic narratives into EFL teaching within a Chinese university setting. Through the self-observation and reflection of a six-class-hour unit on China’s metro development, I analyze my own bilingual teaching approach, using both English and Chinese to clarify concepts, and employing various strategies such as multimedia resources to ensure comprehension and engagement. The study finds that integrating ethnic narratives through culturally relevant content and bilingual instruction effectively promotes student engagement and critical thinking.